High-fructose feeding does not induce steatosis or non-alcoholic fatty liver disease in pigs - Nikolaj H. Schmidt (Nature Portfolio, 2021)
Abstract Non-alcoholic fatty liver disease (NAFLD) is an increasingly prevalent condition that has been linked to high-fructose corn syrup consumption with induction of hepatic de novo lipogenesis (DNL) as the suggested central mechanism. Feeding diets very high in fructose (> 60%) rapidly induce several features of NAFLD in rodents, but similar diets have not yet been applied in larger animals, such as pigs. With the aim to develop a large animal NAFLD model, we analysed the effects of feeding a high-fructose (HF, 60% w/w) diet for four weeks to castrated male Danish Landrace-York-Duroc pigs. HF feeding upregulated expression of hepatic DNL proteins, but levels were low compared with adipose tissue. No steatosis or hepatocellular ballooning was seen on histopathological examination, and plasma levels of transaminases were similar between groups. Inflammatory infiltrates and the amount of connective tissue was slightly elevated in liver sections from fructose-fed pigs, which was corroborated by up-regulation of macrophage marker expression in liver homogenates. Supported by RNA-profiling, quantitative protein analysis, histopathological examination, and biochemistry, our data suggest that pigs, contrary to rodents and humans, are protected against fructose-induced steatosis by relying on adipose tissue rather than liver for DNL.